2021
DOI: 10.1007/s10554-021-02215-1
|View full text |Cite
|
Sign up to set email alerts
|

Aortic strain in bicuspid aortic valve: an analysis

Abstract: Introduction: Bicuspid aortic valve (BAV) is frequently related to aortic valve disease and aortopathy and it is usually monitored by transthoracic echocardiography and computed tomography (CT) angiography. However, early markers of disease progression are not currently available. Speckletracking echocardiography (STE) has shown consistent results among other cardiac pathologies. The present study evaluated STE aortic and left ventricle (LV) strain prognostic value, their discriminative power and their correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In addition, Carlos et al 174 . reported a significant reduction in GLS in patients with bicuspid aortic valve (BAV) in comparison to control group (− 16.0 ± 2.8 vs. − 19.0 ± 1.9, p < 0.001), underlining the subclinical alteration in LV mechanics even without valvulopathy or aortopathy.…”
Section: Principal Clinical Applications Of Left Ventricular Strain A...mentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, Carlos et al 174 . reported a significant reduction in GLS in patients with bicuspid aortic valve (BAV) in comparison to control group (− 16.0 ± 2.8 vs. − 19.0 ± 1.9, p < 0.001), underlining the subclinical alteration in LV mechanics even without valvulopathy or aortopathy.…”
Section: Principal Clinical Applications Of Left Ventricular Strain A...mentioning
confidence: 97%
“…172 After aortic valve replacement, LV deformation shows improvement in all the 3 normal directions. 173 In addition, Carlos et al 174 Finally, GLS provides useful information in the setting of mitral stenosis (MS). It was demonstrated how patients affected by MS present significantly lower absolute GLS values compared to healthy control participants prior to percutaneous balloon mitral valvuloplasty.…”
Section: Valvular Heart Disease (Vhd)mentioning
confidence: 99%
“…In paediatric patients with congenital AS treated with balloon aortic valvuloplasty, post-procedural GLS was lower than in healthy children, with more impaired values in those with LV eccentric hypertrophy or with higher residual aortic gradients [ 35 ]. Carlos et al reported lower GLS values in BAV patients [ 36 ]. Impaired GLS has been observed more frequently in cases of valve dysfunction, with a progressive worsening according to the severity of the valvulopathy, and it has been correlated, even in BAV patients, with the risk of undergoing aortic valve replacement [ 37 ].…”
Section: Diagnostic Imagingmentioning
confidence: 99%